(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2024)
The present study applied a positivist-deductive approach with a causal-comparative research design, using purposive convenient sampling to select four hundred and thirty three participants from different Nepalese academic institutions. An online platform facilitated the administration of a meticulously structured data collection instrument, i.e., structured questionnaire. Descriptive and inferential statistical analysis using SPSS software 24 was conducted. Validity and reliability tests were performed with Amos 22, offering empirical insights into the preparedness of Nepalese academia for the Society 5.0 paradigm shift, which allowed for an in-depth examination of the preparedness of Nepalese educational institutions, contributing to theoretical insights and practical understanding of the interplay between human resources and technology integration. Findings revealed a low level of preparedness among Nepalese academia for transitioning to Society 5.0, particularly in human resources and technology integration. Application of technology in recruitment processes enhanced efficiency and reduced time-to-hire, aligning with Society 5.0 goals. However, a significant gap in digital literacy among faculty members was identified, highlighting the need for resources and training programs to facilitate technology integration into teaching methodologies. Nevertheless, institution advocates for its faculty to adopt innovative teaching methods such as blended learning and flipped classrooms, which are crucial for providing experiential learning opportunities in alignment with Society 5.0 principles. The study provides valuable insights for educational leaders, universities, and policymakers aiming to enhance institutional preparedness for Society 5.0, enriching an understanding of factors influencing preparedness and laying a foundation for impending research in the context of technological and educational advancements in Nepalese Academia.